Digital Audit Guidance to Reduce Program and Finance Manipulation Report with Educational Management System for Administration Affair - Pamuji, Wirawan; Simangunsong, Herlina; Siallagan, Dahlia Nopelina (PT FORMOSA CENDEKIA GLOBAL, 2024)
Administrative malpractice in the creation of deceptive programs is essential to discuss when enhancing school funds and events, as it poses a risk due to potentially misleading reports created by school administrators. In this case, school administration is indicated to involve the use of digital filters to prevent internal corruption related to event and financial reports within the school environment. This is achieved through a development design that incorporates digital or computerized systems to minimize corruption. It is applied to standardize financial reports for school events. In fact, digital auditing tools are not limited to manual implementation but also include automated checks designed to detect and filter discrepancies in reports according to the current standard system.